Implementasi Algoritma J48 Untuk Identifikasi Website Phising - Ryan Putra Ramadhan; Teti Desyani (CV. Shofanah Media Berkah, 2023)
The implementation of the J48 algorithm in phishing website identification is a technique used to predict whether a website falls into the category of phishing or not. The J48 algorithm is one type of Decision Tree solving procedure that is popularly used in the field of data processing and machine learning in the Weka application. In this implementation, the domain link of the website to be identified is analyzed. The phishing website identification process using the J48 solving procedure can increase the effectiveness and efficiency of detecting phishing websites. This is because the J48 solving procedure can form easily understood examples and be used by machines to classify websites. However, in the implementation of the J48 algorithm, high-quality and varied data is required to achieve optimal results. Additionally, the use of this algorithm does not guarantee 100% accuracy in detecting phishing websites, so evaluation and additional features that can accurately predict a site are needed, as well as the need for the combination of other algorithms.